Photoactive RuII-polypyridyl complexes that display sequence selectivity and high-affinity binding to duplex DNA through groove binding - Ghosh, Amrita; Das, Priyadip; Gill, Martin R.; Kar, Prasenjit; Walkar, Michael G.; Thomas, Jim A.; Das, Amitava (Chemistry A European Journal, 2011)
The duplex-DNA binding properties of a nonintercalating polypyridyl ruthenium(II) complex that incorporates a linear extended ligand with a catechol moiety has been probed with a variety of photo- and biophysical techniques. These studies reveal that the complex groove binds to DNA sequences biphasically, and displays binding constants equivalent to those of high-affinity metallointercalators. The complex also displays preferential binding to AT-rich sequences. Changes in the structure of the coordinated catechol ligand and the incorporation of intercalating ancillary ligands into the complex were found to modulate both the optical-binding response and binding parameters of the system, which indicates that the catechol moiety plays a crucial role in the observed enhancement to binding affinities.

Cytostatic ruthenium(II)-platinum(II) bis(terpyridyl) anticancer complex that blocks entry into sphase by up-regulating p27(KIP1) - Ramu, Vadde; Gill, Martin R.; Jarman, Paul J.; Turton, David; Thomas, Jim A.; Das, Amitava; Smythe, Carl (Chemistry-A European Journal, 2015)
Cytostatic agents that interfere with specific cellular components to prevent cancer cell growth offer an attractive alternative, or complement, to traditional cytotoxic chemotherapy. Here, we describe the synthesis and characterization of a new binuclear Ru-II-Pt-II complex [Ru(tpy)(tpypma)Pt(Cl)(DMSO)](3+) (tpy=2,2:6,2-terpyridine and tpypma=4-([2,2:6,2-terpyridine]-4-yl)-N-(pyridin-2-ylmethyl)aniline), VR54, which employs the extended terpyridine tpypma ligand to link the two metal centres. In cell-free conditions, VR54 binds DNA by non-intercalative reversible mechanisms (K-b=1.3x10(5)M(-1)) and does not irreversibly bind guanosine. Cellular studies reveal that VR54 suppresses proliferation of A2780 ovarian cancer cells with no cross-resistance in the A2780CIS cisplatin-resistant cell line. Through the preparation of mononuclear Ru-II and Pt-II structural derivatives it was determined that both metal centres are required for this anti-proliferative activity. In stark contrast to cisplatin, VR54 neither activates the DNA-damage response network nor induces significant levels of cell death. Instead, VR54 is cytostatic and inhibits cell proliferation by up-regulating the cyclin-dependent kinase inhibitor p27(KIP1) and inhibiting retinoblastoma protein phosphorylation, which blocks entry into Sphase and results in G1 cell cycle arrest. Thus, VR54 inhibits cancer cell growth by a gain of function at the G1 restriction point. This is the first metal-coordination compound to demonstrate such activity.
Keywords: antitumor agents; cytostatic; p27KIP1; platinum drugs; ruthenium terpyridine